Assessment Of Seismic Scenario-Structure-Based Limit State Criteria For 23-Storey Of RC High-Rise Building - Che Kamahrudin, Puteri Nihal (Universiti Sains Malaysia, 2018)
Issues regarding to RC high-rise building is different seismic scenario such as near and far-field earthquake can result in difference levels and more complex of seismic scenario structure related to global damage. The objectives of this study are to evaluate the seismic scenario structure for 23-storey of RC high-rise building based on different damage measure and to develop the fragility curve with different limit state criteria. In this study, a 23-storey, 83.95m in height, RC structure is selected as a representative sample building to evaluate the seismic scenario structure. Six ground motions are selected representing two seismic scenarios. Seismic scenario-based building global response at increasing earthquake intensities measure is adopted using Incremental Dynamic Analysis. IDA curves and interstorey drift are the parametric study. The structural performance and damage measure of RC high-rise building were evaluated with the Performance Based Seismic Design (PBSD) limit state. ATC-43 (1998), proposed four performance levels: operational performance (OP), immediate occupancy (IO), life safety (LS), and collapse prevention (CP). Based on the IDA curves, it shows that near field effect has high frequency that gives impact at early intensities measure on building collapsed compared to far field effect. Meanwhile, interstorey drift result indicates that the near field effect has large effect towards the building damage compared to the far field effect. Regarding fragility curves, far field earthquake has larger effect towards the structural damage compared to the near field.